Preservation Mechanism of Carboxymethyl Chitosan Coating on Puffer Fish Quality during Cold Storage - Zhou Ran; Liu Yuan; Xie Jing; Wang Xichang (Zhileng xuebao)
The effects of caboxymethyl chitosan (CMC) coating on the quality of obscure puffer fish (Takifugu obscurus) during storage at 4℃ were studied. Changes in the total viable count of aerobic bacteria, weight loss, total volatile basic nitrogen, trimethylamine, sensory score and the texture indices such as firmness, springiness, resilience and chewiness of the refrigerated puffer fish were investigated. The results showed that compared with the untreated control samples, CMC treatment can suppress bacterial growth, reduce weight loss, and decrease changes in texture indices such as hardness, flexibility, resilience and chewiness, total volatile basic nitrogen, trimethylamine and sensory scores of puffer fish flesh, and extend the shelf life of puffer fish flesh from 4 days to 6 days during cold storage (4℃).